Supplement one new genus and five new species of subfamily Coreinae (Coreidae - Heteroptera) for Vietnam - Khuong, Dang Duc (Academia Journal of Biology, 2014)
The present paper listed one new genus Hydarella Bergroth and five new species: Hydarella orientalis (Disatant), Notobitus excellens Distant, N. elongatus Hsiao, Trematocoris insignis Hsiao and Physomerus parvulus Dall., which are recorded for the first time for Vietnam. Hydarella orientalis (Disatant): Head subquadrate, slightly anteriorly produced; ocelli placed much nearer to eyes than to each other; antennae very long and slender, basal joint as long as the head and pronotum together. Rostrum reaching the posterior coxae. Body ochraceous thickly punctate, the punctures very coarse on the corium. Length: 7 mm. Dist.: Vietnam (Nghean), India, Myanma. Notobitus excellens Distant: Head, antennae and pronotum brassy-black; rostrum extending to about base of mesonotum. Scutellum finely granulate, brownish forwads apex. Corium brown, obscurely and faintly pilose, menbrane brassy brown. Posterior femora considerably incrassated, finly granulous, inwardly obscurenly tuberculate, and with a series of acute tubercles on upper surface, beneath with a strong and curved spine a little beyond middle preceded and followed by some smaller spines. Posterior tibia moderately curved, their inner margin denticulated. Length: 27-32 mm; breadth between pronotal angles: 8-9 mm. Dist.: Vietnam (Phutho), India, China. Notobitus elongatus Hsiao: Close to N. melaegris Fabr., but body narrower, head longer and pronotum with collum black. Length: 20.7 mm. Dist.: Vietnam (Phutho), China. Trematocoris insignis Hsiao: Allied to T. lobipes West., but pronotal lateral lobes straightly produced forward lateral angles acute, and posterior tibiae unicolorously dark. Length: 22.5 mm; width: 7 mm, width beetwen pronotal lateral angles 8.5 mm. Dist.: Vietnam (Laocai), China. Physomerus parvulus Dall.: Head and pronotum ocharaceus, corium brownish. Scutellum black, with a central longitudinal and the margins brownish. Clavus, corium fuscus, membrane piceous. Body benneath and legs ochraceous. Posterior femora and tibia unicolor; posterior tibia with the base and apex, and all the tarsi fuscous; antennae black. Length: 19-21 mm; breadth between pronotal angles: 5.5-6 mm. Dist.: Vietnam (Gialai), Myanma, China, Indonesia.